Increased Preference and Value of Consumer Products by Attentional Selection - Makarina, Nadiia; Hübner, Ronald; Florack, Arnd (Frontiers in Psychology, 2019)
It is usually assumed that individuals base their preferences for products or other items on the utility or value associated with the items. However, there is evidence that the attentional selection of an item alone already modulates the preference for that item. For instance, Janiszewski, Kuo, and Tavassoli (2013, Journal of Consumer Research) used unknown consumer products in a series of studies and found that, in a preference choice task, former target products in a visual-search task were preferred to former distractor products. However, it remained unclear whether such effects can be observed when individuals have pre-existing attitudes towards products and whether attentional-selection can change the perceived value of products. Hence, the aim of the present research was to replicate the attentional-selection effect on choice with known products and examine whether selective attention affects the perceived value of products beyond choosing the items. In two experiments, we replicated the attentional-selection effect on item preference in a choice task. Items that had served as targets in the search task were preferred to previous distractors. Introducing a response deadline in the preference-choice task in Experiment 2 did not further increase this effect. However, the value of former targets was rated higher than that of former distractors. Hence, the present results indicate that attentional selection not only affects preference choices but can also increase the value of attended and selected items.